SISTEM PREDIKSI JUMLAH PENGUNJUNG WISATA PANTAI MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Dian Febrianti, Siti Zumaroh; Harijanto, Budi; Saputra, Pramana Yoga (Jurnal Teknologi Terapan, 2025)
Tourism plays an important role in the economic growth of a region. One of the factors that affect the tourism revenue sector is the number of visitors. An unexpected increase in the number of visitors can cause difficulties for tourism managers in providing the best facilities and comfort and safety for vacationing visitors. A prediction system for the number of visitors is needed as an overview of the level of tourism visitors for the coming period and can provide information to tourism managers to prepare better facilities and infrastructure and be able to manage revenue. Prediction of the number of visitors to Kelapa Beach Tourism can be done by applying the Double Exponential Smoothing method. In this study, the data used were 69 data on the number of monthly visitors to Kelapa Beach Tourism from 2018 to 2024. The test results show that the average minimum MAPE value generated is 16.36%. Based on the MAPE criteria scale, it is included in the good category and it can be concluded that this system helps the Kelapa Beach Tourism management team in predicting the number of visitors in the next period.